Analisis Yuridis Sanksi Pidana Pelanggaran Pasal 281 Jo 77 Ayat (1) Undang Undang Nomor 22 Tahun 2009 Tentang Lalu Lintas Dan Angkutan Jalan Di Wilayah Hukum Polres Serang Kota - Alihamzah, Januar; Irawan, Benny; Herli, Dadang (UI Scholars Hub, 2022)
Law Number 22 Year 2009 concerning Road Traffic and Transportation (LLAJ Law) explains that traffic order and road transportation is a traffic condition that takes place regularly with the rights and obligations of every road user. Every motorized vehicle driver is required to have a driving license (SIM) in accordance with the provisions of Article 77 paragraph (1) of the LLAJ Law. The fact that happened in the jurisdiction of the Serang Kota Police, there were 156 cases of violations of Article 77 paragraph (1) of the LLAJ Law which were decided by the Serang District Court with fines whose value was far from the maximum fine in accordance with Article 281 of the LLAJ Law, and with the same violations there were the fines imposed by the judges are different. This paper will examine the factors that hamper vehicle drivers in obtaining a SIM and the application of criminal sanctions against SIM violations against motor vehicle driver compliance in the jurisdiction of the Serang Kota Police.